2021
DOI: 10.1108/sef-07-2020-0251
|View full text |Cite
|
Sign up to set email alerts
|

Causality-in-mean and causality-in-variance among Bitcoin, Litecoin, and Ethereum

Abstract: Purpose This study aims to examine the volatility spillovers between Bitcoin (BTC), Litecoin (LTC) and Ethereum (ETH) as they are related to structural breaks. Design/methodology/approach This study examines the daily period from August 7, 2015 to July 10, 2018 by conducting causality-in-mean and causality-in-variance tests among cryptocurrencies. Findings The findings showed that there was one-way causality-in-mean from BTC to LTC and ETH, but there was no causality-in-mean from LTC and ETH to BTC. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…negative returns are associated with higher implied volatility than positive ones). These findings are in line with other studies in other asset classes such as commodities (Yip et al, 2020) or cryptocurrencies (Gemici & Polat, 2021) and summarized in the review of key studies on implied volatility undertaken by Fassas and Siriopoulos (2021).…”
Section: Literature Reviewsupporting
confidence: 91%
“…negative returns are associated with higher implied volatility than positive ones). These findings are in line with other studies in other asset classes such as commodities (Yip et al, 2020) or cryptocurrencies (Gemici & Polat, 2021) and summarized in the review of key studies on implied volatility undertaken by Fassas and Siriopoulos (2021).…”
Section: Literature Reviewsupporting
confidence: 91%
“…Zhang and Wang (2020) analyzed the relationship between twenty cryptocurrencies and investor attention and stated that they observed a bidirectional causal relationship between cryptocurrency returns and investors' attention. Gemici and Polat (2021) examined the volatility spillovers between Bitcoin, Litecoin and Ethereum and reported that they observed a one-way causality running from Bitcoin to both Litecoin and Ethereum. Li et al (2021) investigated the relationship between investor attention and cryptocurrency returns.…”
Section: Ui̇i̇i̇d-ijeas 2022 (34):129-142 Issn 1307-9832mentioning
confidence: 99%
“…Therefore, considering recent experience, reckless entry by the banking sector into Fintech development, and the desire to incorporate such veiled risks for diversification and profitability, should perhaps be considered with caution in light of recent sectoral fragility. Perhaps, substantive evidence of irrational exuberance should act as a warning to the inherent risks incorporated (Cheah and Fry, 2015; Gandal et al , 2018; Corbet et al , 2018; Griffin and Shams, 2020; Gemici and Polat, 2020; Andrade et al , 2021; Hazgui et al , 2021), with a revised warning that the traditional banking sector should not forget recent lessons of the past and that their primary duty and service to the customer is that of banking. However, we weigh this concern with the caveat that the only way to progress an entire sector is through exploration and some moderate risk-taking.…”
Section: Introductionmentioning
confidence: 99%